A multi-country, cross-sectional observational study of retinopathy of prematurity in Latin America and the Caribbean - Lauren Arnesen; Pablo Durán; Juan Silva; Luisa Brumana
ABSTRACT Objective To consolidate available information from the Latin American and Caribbean (LAC) region on 1) national incidence of retinopathy of prematurity (ROP) and 2) national-level government inputs on ROP (existing national policies, guidelines, programs, and financing for ROP prevention, detection, and treatment, including ROP screening) in 2014. Methods In March and April 2015, a multi-country online survey was distributed to 56 medical and public health experts working on ROP in LAC countries. Respondents were instructed to provide quantitative and qualitative information representative of the national situation in 2014 for ROP incidence and national-level government inputs (existing national policies, guidelines, programs, and financing for ROP prevention, detection, and treatment, including ROP screening) in their country. Results The survey was completed in full by a total of 11 experts from 10 LAC countries (Argentina, Brazil, Colombia, Costa Rica, Cuba, Dominican Republic, El Salvador, Mexico, Nicaragua, and Panama). According to the survey results, six countries had a national policy that includes ROP prevention, detection, and treatment, with screening and treatment covered by national/federal funding. Eight countries had national guidelines for ROP. Four countries had legislation mandating eye examination of preterm infants. Most countries had Level 3 and 4 neonatal intensive care units with ROP programs in public sector health care facilities. Five countries had a data collection or monitoring system to track the number of newborn babies screened for ROP within hospital settings. On average, countries with three or four of the above-mentioned ROP elements screened 95% of eligible newborns in 2014, while those with only one or two of the ROP elements screened 35% of eligible newborns. Conclusions National government buy-in and involvement in ROP screening and treatment legislation is related to a higher proportion of eligible premature newborns being screened and treated for ROP. Further research should include more countries and assess national-level engagement with ROP, including ROP screening and treatment.